The effects of market integration on pollution: an analysis of EU enlargements - Konstantin Sommer; Henri L.F. de Groot; Franc Klaassen (Tinbergen Institute, 2022)
We study the effects of market integration on manufacturing emission intensities of CO2, SOx, and NOx. For this, we analyse the 2004 and 2007 EU enlargements in a sub-sectoral panel with data on almost all EU member states from 1995 to 2015. We pay close attention to relevant channels of trade, regulation, and efficiency. Overall, the enlargements have resulted in a reduction of emission intensities in new member states: new regulations, which accession countries needed to adopt, have lowered pollution intensities strongly; induced improvements in productivity have further reduced them; and trade integration into the EU has had insignificant effects on emission intensities. We also do not find evidence of within-EU pollution haven effects and thus of leakage from old to new member states. For old mem- bers, trade integration, if anything, increased emission intensities, but efficiency improvements have also contributed to cleaner manufacturing sectors here.
Keywords: F15; F64; Q56; 330; Market Integration; EU Enlargement; Carbon Leakage; Pollution Havens; Emission Intensity